Gestión habitacional estatal en áreas de interfase: Reflexiones sobre el acceso a la tierra, la vivienda y a un hábitat digno - Blanco Avila, Ana María; Dalla Torre, Julieta (Pontificia Universidad Católica del Perú, 2025)
In San Juan, Argentina, the beginning of the new millennium was marked by a strong state territorial intervention mainly linked to the development of housing policies that defined the use and distribution of urban land, and the access to basic goods and services by its population. The article reflects on the regularization policies of the southwest interface of the San Juan Metropolitan Area in the last two decades, in the framework of the state housing relocation processes developed, and their relevance in the access to housing and land, as well as in the construction of democratic and sustainable territories that ensure social and environmental justice to their inhabitants. In this context, we ask: what were the characteristics of these public policies, were there differences between the policies of the beginning of the century and those of the last decade, and what were the social implications of these processes? The methodological strategy involved the adoption of a largely qualitative perspective that combined documentary, conversational and observational techniques. The main finding relates to the housing policies implemented and the resulting improvements in access to land and housing for the most vulnerable sectors, despite persistent deficiencies in access to decent housing.

En la provincia de San Juan, el inicio del nuevo milenio estuvo marcado por una fuerte intervención territorial estatal vinculada principalmente al desarrollo de políticas habitacionales en las que se definió el uso y distribución de la tierra urbana, y el acceso a bienes y servicios fundamentales por parte de su población. El artículo reflexiona acerca de las políticas de regularización en la interfase suroeste del Área Metropolitana de San Juan en las últimas dos décadas, en el marco de los procesos de relocalización habitacional estatal desarrollados, y su relevancia en el acceso a la vivienda y a la tierra, así como en la construcción de territorios democráticos y sostenibles que aseguren la justicia social y ambiental a sus pobladores. En este contexto, nos preguntamos: ¿qué características presentaron estas políticas públicas?, ¿existieron diferencias entre las políticas de principios de siglo y las de la última década?, ¿qué implicancias en el tejido social tuvieron dichos procesos? La estrategia metodológica implicó la adopción de una perspectiva mayormente cualitativa que combinó técnicas documentales, conversacionales y observacionales.
State Housing Management in Interface Areas: Reflections on Access to Land, Housing and a Dignified Habitat
Keywords: Housing policies; Relocations; Habitat; Access to land and housing; Interface territories; Políticas habitacionales; Relocalizaciones; Hábitat; Acceso a la tierra y la vivienda; Territorios de interfase; https://purl.org/pe-repo/ocde/ford#5.04.00